Saccharomyces cerevisiae L-BC double-stranded RNA virus replicase recognizes the L-A positive-strand RNA 3' end. - Ribas, J C (1996)
L-A and L-BC are two double-stranded RNA viruses present in almost all strains of Saccharomyces cerevisiae. L-A, the major species, has been extensively characterized with in vitro systems established, but little is known about L-BC. Here we report in vitro template-dependent transcription, replication, and RNA recognition activities of L-BC. The L-BC replicase activity converts positive, single-stranded RNA to double-stranded RNA by synthesis of the complementary RNA strand. Although L-A and L-BC do not interact in vivo, in vitro L-BC virions can replicate the positive, single-stranded RNA of L-A and its satellite, M1, with the same 3' end sequence and stem-loop requirements shown by L-A virions for its own template. However, the L-BC virions do not recognize the internal replication enhancer of the L-A positive strand. In a direct comparison of L-A and L-BC virions, each preferentially recognizes its own RNA for binding, replication, and transcription. These results suggest a close evolutionary relation of these two viruses, consistent with their RNA-dependent RNA polymerase sequence similarities.